V.G. Grynevetskyy as a reformer of higher technical education - Kostenko, A. I. (History of science and technology, 2014)
Grynevetskyy Vasil Gnatovych (1871-1919) - scientist, engineer and heating engineer, worker professional education. After graduating from the Moscow Higher Technical School (1896) was left there as a teacher; Professor (1900), Director of the College (1914-1918). Submitted a project to convert College High School Polytechnic type. Member of the Russian Technical Society. At the 3rd Congress of leaders of technical and vocational education (1903) presented a report on the experimental (laboratory) method of teaching. In 1916 proposed a reform of vocational education, which defended the necessity of increasing specialization and «double» specialization (production and functional) and the rejection of universalism, professional orientation general cycle. Proposed economically convenient grouping specialties, organizing laboratories and workshops. However, its design is not enough space given to education. In August 1917 led committee to convene the 4th All-Russian Congress of vocational education. Together with representatives of higher technical school (D.S. Zernov, V. N. Obrazcov) opposed the transfer of technical schools under the jurisdiction of People’s Commissariat and defended depoliticization vocational school. He emphasized the need for specialization, was to «weave» vocational education with general, regarded as the principle of putting Polytechnic extra «encyclopedic». At the same time, in a period of underestimating this People’s Commissariat of professional education concerns many old professors confirmed. Opinion V.G. Grynevetskyy denied by the People’s Commissariat (M.M. Pokrovsky, I.N. Kuzmin et al.) That popularized professional formation of a new type.